Association between neutrophil count and the risk of cardiovascular disease: A community-based cohort study in Taiwan - Kuang-Chung Wang; Chu-Lin Lin; Chun-Chieh Lin; Yun-Tzu Lee; Le-Yin Hsu; Kuo-Liong Chien; Tzu-Lin Yeh (PLoS ONE, 2025)
Background Neutrophil count is associated with atherosclerotic plaque formation and cardiovascular diseases (CVD). As previous studies have been predominantly conducted in Caucasians, the significance of neutrophil count as a clinical factor in CVD in other ethnicities remain unclear. Methods A total of 2,955 participants from the Chin-Shan Community Cardiovascular Study(CCCC), who had no established CVD diagnosis and missing data, were enrolled in this study and followed from 1990–1991–2013. We use Cox regression models to calculate hazard ratio (HR) and 95% confidence interval (CI) to evaluate the association between neutrophil count and CVD risk. Subgroup analyses were performed based on sex and age, while sensitivity analyses were conducted by excluding participants with extreme values. Results Over a median follow-up period of 22 years, 400 cases of new-onset CVD were recorded. Cox proportional hazards regression analysis revealed that a higher neutrophil count was independently associated with CVD incidence in Taiwanese adults, with an HR of 1.42 (95% CI 1.03–1.94) after adjusting for multiple covariates. This association remained consistent in both the subgroup and sensitivity analyses. Conclusion Our study demonstrated that, in the Taiwanese population, a higher neutrophil count was associated with a higher incidence of CVD over an average 22-year follow-up in individuals without preexisting CVD.